STRATEGI PENGELOLAAN HUMAS BERBASIS KOMUNITAS DALAM MEMPERKUAT IDENTITAS SEKOLAH DI MASYARAKAT - Deli Wulandari; Abdullah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
In the context of an increasingly competitive educational landscape, it is imperative for educational institutions to cultivate a robust identity and garner public trust, which can be facilitated through the implementation of community-oriented public relations management strategies. This research endeavor seeks to elucidate the execution of community-centered public relations strategies aimed at fortifying school identity within the local populace. The methodological framework employed in this inquiry is qualitative in nature, utilizing a descriptive design. Data collection encompassed comprehensive interviews with the principal, educators, and parents, alongside direct observations of school-related activities and the examination of documentation pertinent to public relations initiatives. The results indicate that the institution engages in open communication through direct socialization and transparent dissemination of information, thereby allowing the community to actively monitor school operations and student progress, which in turn cultivates public trust. These practices align with the principles of two-way communication and public transparency theories.Nevertheless, community engagement appears to be relatively passive, as the local populace has not been fully integrated as a proactive partner in the planning and assessment of educational programs. The study concludes that community-centric public relations management significantly bolsters school identity, yet necessitates the adoption of more participatory and sustainable strategies